PRINTING ARABIC BOOKS IN EUROPE 1475 – 1710 - Waisy, karwan (Humanities Journal of University of Zakho, 2024)
This period of printing and translating Arabic books in Europe (1475-1710) is considered as a “significant and preliminary phase” of printing books in Arabic language in Europe. Hence, this article is allocated to depict the printing books in Arabic language process. This article pays a great attention to the written language of Quran and Arabic grammar in Europe. This subject is been regularly ignored, and Kurdish academic institutions have begun to pay attention to it. As a result, this research attempts to clarify some historical development and new assessment of i. This study has taken most attention to the printing process, types of printings, and other aspects of it. The article uses some key articles and reports, which are published in English language. The objective of this research is to show the most important Arabic books that have been printed in Europe and the European aims of printing these books. Most of the Arabic books printed by Europeans were related to Islam and Arabic grammar. This raises key questions why European paid most attention to the printing and translating Arabic accounts. According to this premise, this research aims to answer some crucial questions that are related to this study, such as: Why the European paid most attention to printing and translating Arabic books? What subjects and issues were these books related to? Were Europeans seeking to benefit from those books, or were they attempting to critique Islam and the Arabic language? Did the printing and translating Arabic books have effects on the emergence of ideas in the Arabic World?